2009
DOI: 10.1007/s00259-009-1195-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of hypoxia with radiolabelled agents

Abstract: Tissue hypoxia results from an inadequate supply of oxygen (O 2 ) that compromises biological functions. Structural and functional abnormalities of the tumour vasculature together with altered diffusion conditions inside the tumour seem to be the main causes of tumour hypoxia. Evidence from experimental and clinical studies points to a role for tumour hypoxia in tumour propagation, resistance to therapy and malignant progression. This has led to the development of assays for the detection of hypoxia in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 94 publications
(104 reference statements)
2
145
0
3
Order By: Relevance
“…19 Moreover, the use of Tc-99m-HL91 has been described for identifying tumor hypoxia in vitro and ex vivo. 17,[19][20][21][22][23][24] The present study demonstrates for the first time, to our knowledge, that Tc99m-HL91 is useful as an imaging biomarker to predict the treatment responses of hypoxia-regulated CD/5-FC gene therapy in a mouse lung tumor model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Moreover, the use of Tc-99m-HL91 has been described for identifying tumor hypoxia in vitro and ex vivo. 17,[19][20][21][22][23][24] The present study demonstrates for the first time, to our knowledge, that Tc99m-HL91 is useful as an imaging biomarker to predict the treatment responses of hypoxia-regulated CD/5-FC gene therapy in a mouse lung tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…18 In vitro studies have identified hypoxia-selective uptake of Tc-99m-HL91, with a significant increase in the uptake in the hypoxic state compared with the normoxic state. 17,19,20 Animal studies have also shown that Tc99m-HL91 is markedly increased in mice treated with hydralazine compared with controls. 19,20 The aim of this study was to test our hypothesis that Tc-99m-HL91 imaging can be used to identify the efficacy of hypoxia-induced CD gene/5-FC gene therapy for cancer.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, tirapazamine, an aromatic heterocycle di-N-oxide, is reduced to toxic radicals in hypoxic conditions and results in DNA breaks [83]. Many PET tracers have been developed to image tumor hypoxia in vivo [84][85][86][87][88]. Among them, nitroimidazole compounds are promising imaging probes to report severe hypoxia, which become reduced in a hypoxic environment and then covalently bind to intracellular macromolecules (Fig.…”
Section: Hypoxia Pet Imagingmentioning
confidence: 99%
“…The important ones include hypoxia markers (FMISO, FAZA, Cu-ATSM, and others), [66] proliferation markers (C-11-L-methionine, 2-[C-11]-thymidine, F-18-FDOPA), [67,68] necrosis marker (F-18-labeled 5-fluoropentyl-2-methyl-malonic acid), [69] apoptosis markers (4-[ 18 F]fluorobenzoylannexin V, Cu-DOTA-Annexin V), [70] and angiogenesis markers (RGD-peptides, 15 O-H 2 O) [71,72]. However, the use of these uncommon radiopharmaceuticals has been limited to a small number of academic centers, and it will take time until one of them becomes a PET marker that maps one physiological process important for the definition of a biological sub-volume.…”
Section: Potentials Of Fdg As a Radiopharmaceutical For Radiotherapy mentioning
confidence: 99%